SELF REGULATED LEARNING DAN OPTIMISME KARIER TERHADAP ADAPTABILITAS KARIER PADA MAHASISWA TINGKAT AKHIR - Adinda Zakila; Lucky Purwantini (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2022)
This study aims to determine the relationship and influence between self-regulated learning and career optimism in final year students. This research uses quantitative method with correlational type. The subjects in this study were final year students at the Islamic University 45 Bekasi with a sample of 88 respondents. This study uses a self-regulated learning scale with Cronbach's alpha reliability value, the value of ralpha = 0.935, the career optimism scale of ralpha = 0.858, and the career adaptability scale of ralpha = 0.950. The results of data analysis obtained a value of p = 0.000 (p <0.05), which means that there is a significant relationship between self-regulated learning and career adaptability in final year students and a correlation coefficient of 0.538 is obtained. Meanwhile, in the Spearman rank correlation test between career optimism and career adaptability, the results showed that there was no relationship with a correlation coefficient of -0.163 and p value = 0.129 (p>0.05). Then for the simple linear regression test, the R correlation value is 0.294. And obtained the value of the coefficient of determination (R2) of 0.322 which means that there is an influence of the variable self-regulated learning on career adaptability with a percentage of 29.4% while 70.6% is influenced by other variables not examined in this study.